Model evaluation of the atmospheric boundary layer and mixed-layer evolution - Tombrou, Maria; Dandou, Aggeliki; Helmis, Costas; Akylas, Evangelos; Angelopoulos, George; Flocas, Helena; Assimakopoulos, Vasiliki; Soulakellis, Nikolaos (My University, 2007)
In the present study, an attempt is made to assess the atmospheric boundary-layer (ABL) depth over an urban area, as derived from different ABL schemes employed by the mesoscale model MM5. Furthermore, the relationship of the mixing height, as depicted by the measurements, to the calculated ABL depth or other features of the ABL structure, is also examined. In particular, the diurnal evolution of ABL depth is examined over the greater Athens area, employing four different ABL schemes plus a modified version, whereby urban features are considered. Measurements for two selected days, when convective conditions prevailed and a strong sea-breeze cell developed, were used for comparison. It was found that the calculated eddy viscosity profile seems to better indicate the mixing height in both cases, where either a deep convective boundary layer develops, or a more con- fined internal boundary layer is formed. For the urban scheme, the incorporation of both anthropogenic and storage heat release provides promising results for urban applications.
Keywords: Atmospheric boundary layer; Eddy viscosity; Entrainment layer; Mixing height; MM5 model; Sea breeze